2022
DOI: 10.3389/fmed.2022.820281
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of the Albumin to Fibrinogen Ratio in Peritoneal Dialysis Patients

Abstract: BackgroundAlbumin to fibrinogen ratio (AFR) is a demonstrated predictor of mortality in various diseases. The aim of this study was to evaluate the prognostic value of AFR to predict mortality in peritoneal dialysis (PD) patients.MethodsWe retrospectively analyzed 212 incident PD patients from January 2010 to December 2017 and followed them until December 2019. We used receiver operating curve (ROC) analysis to determine the optimal cut-off point for AFR at baseline to predict overall and cardiovascular mortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Xia et al. found that patients undergoing PD with a high albumin to fibrinogen ratio had reduced all-cause and cardiovascular mortality [ 7 ]. In our study, we found that plasma fibrinogen was an independent risk factor for LV remodeling in patients undergoing PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Xia et al. found that patients undergoing PD with a high albumin to fibrinogen ratio had reduced all-cause and cardiovascular mortality [ 7 ]. In our study, we found that plasma fibrinogen was an independent risk factor for LV remodeling in patients undergoing PD.…”
Section: Discussionmentioning
confidence: 99%
“…According to statistics, the prevalence of LVH in patients on hemodialysis or PD is approximately 75% [ 5 ]. Recently, plasma fibrinogen level has been proven to be significantly associated with an increased risk of cardiovascular events and all-cause mortality in patients on PD [ 6 , 7 ]. Of note hyperfibrinogenemia is common among patients treated with dialysis, especially in those on PD.…”
Section: Introductionmentioning
confidence: 99%